2021
DOI: 10.1186/s12877-021-02022-2
|View full text |Cite
|
Sign up to set email alerts
|

Disability, Frailty and Depression in the community-dwelling older adults with Osteosarcopenia

Abstract: Background The purpose of this study was to investigate the prevalence of osteosarcopenia in the over 60-year-old community and to evaluate whether osteosarcopenia is associated with disability, frailty and depression. Methods This study was performed using the baseline data of Namgaram-2, among the 1010 surveyed subjects, 885 study subjects who were 60 years or older and had all necessary tests performed were selected. The Kaigo-Yobo checklist (fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The latter was also highlighted by Reiss and colleagues [ 40 ] and Okayama and colleagues [ 41 ] who add low quality of life as a risk factor for OS. Park [ 42 ] found that osteosarcopenic patients have greater frailty and disabilities in everyday life and worse depression. The results of another study [ 43 ] reinforced the above risk factors with osteosarcopenic patients preesnting as older and frailer with a lower BMI, fat and muscle mass, handgrip strength, and T-score compared to non-osteosarcopenic patients.…”
Section: Clinical Studies On Osteosarcopenia and Associated Risk Factorsmentioning
confidence: 99%
“…The latter was also highlighted by Reiss and colleagues [ 40 ] and Okayama and colleagues [ 41 ] who add low quality of life as a risk factor for OS. Park [ 42 ] found that osteosarcopenic patients have greater frailty and disabilities in everyday life and worse depression. The results of another study [ 43 ] reinforced the above risk factors with osteosarcopenic patients preesnting as older and frailer with a lower BMI, fat and muscle mass, handgrip strength, and T-score compared to non-osteosarcopenic patients.…”
Section: Clinical Studies On Osteosarcopenia and Associated Risk Factorsmentioning
confidence: 99%
“…In contrast, Han et al [ 35 ] showed that low handgrip strength was significantly associated with depressive symptoms in socially deprived Korean older adults. In a recent study involving 885 community-dwelling older adults, Park et al [ 36 ] found that osteosarcopenia, which was defined as the presence of low bone mineral density in addition to low ASM and low MF, was significantly associated with health problems such as disability, frailty, and depression. Together, the findings from the current and previous studies have showed that loss of MF or, preferably, the coexistence of low ASM and low MF is a better predictor of depression in geriatric populations, supporting the use of the sarcopenia criteria recommended by the AWGS [ 6 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with osteosarcopenia have an increased risk of falls and fractures, resulting in a poor quality of life and increased mortality [ 81 , 82 ]. The prevalence of osteosarcopenia in community-dwelling older adults is 8.4 %, 12.7%, and 19.2 % in Japan, China, and Korea, respectively [ 11 , 12 , 13 ]. In a Korean study of patients aged ≥60 years with hip fractures, the prevalence of osteosarcopenia was 28.7%, and the 1-year mortality of osteosarcopenia (15.1%) was higher than that of the normal (7.8%), osteoporosis-alone (5.1%), and sarcopenia-alone (10.3%) groups [ 83 ].…”
Section: Osteosarcopenia In Chronic Liver Diseasementioning
confidence: 99%
“…In a Korean study of patients aged ≥60 years with hip fractures, the prevalence of osteosarcopenia was 28.7%, and the 1-year mortality of osteosarcopenia (15.1%) was higher than that of the normal (7.8%), osteoporosis-alone (5.1%), and sarcopenia-alone (10.3%) groups [ 83 ]. Furthermore, patients with osteosarcopenia had higher scores for disability, frailty, and depression than those without it [ 13 ]. A recent pooled analysis of the aging general population demonstrated that osteosarcopenia increases the risk of fractures [odds ratio (OR), 2.46], falls (OR, 1.62), and mortality (OR, 1.66) [ 84 ].…”
Section: Osteosarcopenia In Chronic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation